ANOTASI PUTUSAN MAHKAMAH KONSTITUSI NOMOR 20/PUU-XIV/2016 - Aditya Wiguna Sanjaya (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2021)
The status of the state of law attached to the state of Indonesia carries juridical implications that absolutely must be upheld. Every government and state life must rely on the rule of law. Law enforcement becomes a vehicle for the state to ensure the establishment of the law without neglecting human rights protections that serve as a counterweight to state power from the possibility of arbitrariness. Every citizen has the right to privacy (privacy rights) that must be protected by the state. The restoration of the right to privacy should be given strict arrangements in the law including the implications of violations of privacy rights related to whether or not it can be used as evidence in legal proceedings. Such a regulation is absolutely necessary, considering that the law will always be left behind with the development of society, especially the rigid state law demanding the role of judicial institutions in this context is the Constitutional Court to be present to provide solutions for the justice-seeking community through its authority and role as a constitutional guard (the guardian of the constitution), in order to ensure the protection of the constitutional rights of citizens. The formulation of the issue raised is (1) Is the decision of the Constitutional Court Number 20 / PUU-XIV / 2016 appropriate , (2) What is the decision of the Constitutional Court No. 20/PUU-XIV/2016 when viewed from the perspective of Religiousity of Science? This type of research uses juridical-normative methods with a conceptual approach. Results obtained (1) Putusan MK No. 20/PUU-XIV/2016 when viewed from the perspective of State Theory of Law, Theory of Legal Certainty, Theory of Proof, and Hemeneutics of law is very appropriate, (2) The conclusion of MK Number 20 /PUU-XIV/2016 in the perspective of religiousity of science has reflected the elaboration of religious values derived from the revelation of Allah SWT. Keywords: MK’s verdict, evidence, religiousity of science.